1973
DOI: 10.1002/ajpa.1330380304
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of agenesis and polygenesis in the primate dentition

Abstract: The incidence of dental agenesis and polygenesis was demonstrated in 978 Old World monkeys, 390 great apes, 194 lesser apes and 5,000 humans of Caucasoid and Negroid stock. The frequency of agenesis was highest in the human sample, particularly in the Negroids, that of polygenesis was highest in the great apes. Within both groups, the polymorphism was commonest in the molar (predominantly third molar) region. Despite numerous difficulties in the interpretation of such data, on the basis of the differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 39 publications
0
35
1
Order By: Relevance
“…This type of rapid tooth wear is not uncommon among the Beza Mahafaly ring-tailed lemurs Sauther, 2004, 2006]. We also documented 4 examples (blue 127 and blue 136, green 459 and green 209) of dental agenesis (the congenital absence of a tooth [Lavelle and Moore, 1973]) in the Beza Mahafaly population. At Tsimanampesotse National Park, 3 of 25 individuals exhibited agenesis.…”
Section: Dental Variationmentioning
confidence: 79%
See 1 more Smart Citation
“…This type of rapid tooth wear is not uncommon among the Beza Mahafaly ring-tailed lemurs Sauther, 2004, 2006]. We also documented 4 examples (blue 127 and blue 136, green 459 and green 209) of dental agenesis (the congenital absence of a tooth [Lavelle and Moore, 1973]) in the Beza Mahafaly population. At Tsimanampesotse National Park, 3 of 25 individuals exhibited agenesis.…”
Section: Dental Variationmentioning
confidence: 79%
“…For example, Lavelle and Moore [1973] reported an 11.1% frequency of agenesis in modern humans, and a 7.9% frequency in Colobus. Jablonski [1992] reported a 33.3% frequency of premolar agenesis in a sample of Rhinopithecus roxellana.…”
Section: Dental Variationmentioning
confidence: 99%
“…In particular, in 350 specimens of macaques (M. mulatta, M. sinica, and M. irus (= M. fascicularis)), they detected no case of molar agenesis. Although Lavelle and Moore (1973) did not indicate which molars were missing, they stated that the anomalies in the molar teeth were almost all in the third molar region. Hence, congenitally missing first molars must be an extremely rare phenomenon in non-human primates, if it occurs at all.…”
Section: Discussionmentioning
confidence: 97%
“…When molars are congenitally missing, nearly all the cases are upper or lower third molars. Lavelle and Moore (1973) reported prevalence of tooth agenesis in extant primates. Their data indicated that molar agenesis is quite rare in non-human primates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation